Chimeromyiidae, a new family of Eremoneuran Diptera from the Cretaceous - Grimaldi, David A.; Cumming, Jeffrey M.; Arillo, Antonio (Zootaxa, 2009)
A new family of eremoneuran Brachycera, the Chimeromyiidae, is proposed for two genera and eight species of a distinctive, monophyletic group of flies in 125–100 myo amber. The new family is related to the Empidoidea and basal Cyclorrhapha. Four new species of Chimeromyia are described: C. pilitibia Grimaldi and Cumming (in Lebanese amber), C. mediobscura Grimaldi and Cumming, C. alava Arillo and Grimaldi (in Spanish amber), and C. burmitica Grimaldi and Cumming (in Burmese amber). A new genus, Chimeromyina Arillo and Grimaldi is also described, for a primitive new species C. concilia (in Spanish amber). New details of these flies are described, particularly of male and female terminalia, and the relationships between this and other eremoneuran families are discussed.